2006
DOI: 10.1021/ma060328y
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Chain Exchange Kinetics of Diblock Copolymer Micelles:  Tuning and Logarithmic Relaxation

Abstract: A systematic study of the equilibrium chain exchange kinetics of a tunable model system for starlike polymeric micelles is presented. The micelles are formed by well-defined highly asymmetrical poly-(ethylene-propylene)-poly(ethylene oxide) (PEP-PEO) diblock copolymers. Mixtures of N,N-dimethylformamide (DMF) and water are used as selective solvents for PEO. With respect to PEP this solvent mixture allows the interfacial tension, γ, to be tuned over a wide range. The equilibrium chain exchange between these mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
275
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(297 citation statements)
references
References 39 publications
22
275
0
Order By: Relevance
“…In contrast, the exchange rate is significantly faster at higher temperatures. These results resemble observations on self-assembled polymeric micelles, in which monomer expulsion and insertion is the rate-determining step of system dynamics (20,21). Moreover, monomer polymerization and depolymerization are reported to be the main exchange mechanism of supramolecular polymers in organic solvents (22).…”
Section: Resultssupporting
confidence: 82%
“…In contrast, the exchange rate is significantly faster at higher temperatures. These results resemble observations on self-assembled polymeric micelles, in which monomer expulsion and insertion is the rate-determining step of system dynamics (20,21). Moreover, monomer polymerization and depolymerization are reported to be the main exchange mechanism of supramolecular polymers in organic solvents (22).…”
Section: Resultssupporting
confidence: 82%
“…DOI: 10.1103/PhysRevLett.102.188301 PACS numbers: 82.35.Jk, 61.05.cf, 82.35.Lr, 82.70.Uv An archetypical example and a model system for self assembly is the family of amphiphilic A-B diblock copolymers that undergo micellization in aqueous solutions [1,2]. In such systems where the interfacial energy is usually large, the structure formation may be influenced by prominent kinetic barriers leading to a variety of trapped metastable states unable to reach their global equilibrium [3][4][5][6][7][8]. Despite recent progress on manipulation of nonequilibrium structures via kinetic control, such as by sophisticated mixing protocols [6,9,10], a complete understanding of the physical mechanisms of the self-assembly process is still lacking.…”
mentioning
confidence: 99%
“…Extensive previous studies have shown that these asymmetric PEP-PEO diblock copolymers form well-defined starlike micelles in water-dimethylformamide (DMF) solvent mixtures [7,8,21,22]. This solvent pair provides a strong selectivity for PEO; however, since water and DMF have very different interfacial tensions towards the insoluble PEP block ( % 46 and 8 mN=m respectively) [21], the interfacial energy can be easily tuned by varying the composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively polar copolymers and surfactants that readily dissolve in water form rather dynamic micelles with unimeric exchange rates up to the microsecond time scale [29,30]. Encapsulated compounds in such micelles will also be released rapidly because usage as drug delivery systems is always accompanied with significant dilution.…”
Section: Introductionmentioning
confidence: 99%